2010
DOI: 10.1590/s0101-20612010000300014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação bioquímico-nutricional de uma linhagem de soja livre do inibidor de tripsina Kunitz e de lectinas

Abstract: A produção nacional de soja (Glycine max L. Merrill) destina-se, em sua maior parte, à obtenção de óleo e farelo. No Brasil, o consumo do farelo de soja está restrito às indústrias de ração para animais (MONTEIRO et al., 2003). Para esta finalidade, a soja não pode ser utilizada sem tostagem, principalmente quando utilizada na alimentação de animais monogástricos, devido à presença de fatores antinutricionais no grão, os quais interferem na absorção e aproveitamento de nutrientes, limitando o valor nutricional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
5
0
4
Order By: Relevance
“…For to pigs deprecreased ADG by 78% for CSB, 60% for LF, and 35% for LFKF compared with the ADG achieved by pigs fed the same variety but extruded. This results and others (Brune et al, 2010;Becker-Ritt et al, 2004;Vasconcelos et al, 1997) prove that variability in the amounts of these components (proteases inhibitors and lectins) can be affect by cultivars differences. As observed, there seems great potential for reduction in content of anti-nutrients within GM soybeans, as studies have shown that the isogenic variant lacking the Kunitz trypsin inhibitor and other soybean variants low in Kunitz trypsin inhibitor are nutritionally superior to conventional raw soybeans but not as good as commercial soybean meal.…”
Section: Storage and Genetic Varietysupporting
confidence: 75%
“…For to pigs deprecreased ADG by 78% for CSB, 60% for LF, and 35% for LFKF compared with the ADG achieved by pigs fed the same variety but extruded. This results and others (Brune et al, 2010;Becker-Ritt et al, 2004;Vasconcelos et al, 1997) prove that variability in the amounts of these components (proteases inhibitors and lectins) can be affect by cultivars differences. As observed, there seems great potential for reduction in content of anti-nutrients within GM soybeans, as studies have shown that the isogenic variant lacking the Kunitz trypsin inhibitor and other soybean variants low in Kunitz trypsin inhibitor are nutritionally superior to conventional raw soybeans but not as good as commercial soybean meal.…”
Section: Storage and Genetic Varietysupporting
confidence: 75%
“…In vitro digestion patterns of bovine β-Lactoglobulin (β-Lg) fibrils demonstrated that there was no change in the digestion time, from 0.5 to 30 min in native state conditions at SGF, and that there was no β-Lg band intact during the heat treatment (Bateman et al, 2010). The time of 40 min was enough for the entire inactivation process of soybean protease inhibitors and lectins (Brune et al, 2010). Kumar et al (2014) showed that the leucoagglutinating phytohemagglutinin (PHA-L) was resistant to pepsin for up to 60 min.…”
Section: Discussionmentioning
confidence: 99%
“…Os inibidores de proteases na soja são constituídos pelo inibidor de tripsina Kunitz e pelo inibidor de tripsina e quimiotripsina Bowman-Birk. São classificados em duas principais categorias: os de alto peso molecular (cerca de 20.000 kDa), que apresentam duas pontes dissulfeto, 181 resíduos de aminoácidos e possuem especificidade primária para tripsina e os de peso molecular entre 6.000 e 10.000 kDa com alta proporção de ligações dissulfeto, 71 resíduos de aminoácidos e capacidade para inibir tripsina e quimiotripsina em sítios de ligações independentes [39] . Cerca de 80% da inibição da atividade tríptica de grãos de soja é causada pela ação do inibidor de tripsina Kunitz.…”
Section: Inibidores De Proteasesunclassified
“…Foi realizado um estudo pelo Programa de Melhoramento da Qualidade e do Sabor da Soja do BIOAGRO (PMQS), da Universidade Federal de Viçosa (UFV), para o desenvolvimento de uma linhagem de soja com ausência de Inibidores de Tripsina Kunitz (KTI) e lectina (LEC) em suas sementes. A retirada genética do KTI e LEC teve um impacto positivo na digestibilidade das proteínas da soja, no entanto, não melhorou a sua qualidade nutricional [39] .…”
Section: Efeito Do Processamento Nos Fatores Antinutricionaisunclassified
See 1 more Smart Citation